A multicenter study on practices and related factors of traditional medicinal plant use during pregnancy among women receiving antenatal care in East Gojjam Zone, Northwest Ethiopia - Wondemagegn, Amsalu Taye; Seyoum, Girma (Frontiers in Public Health, 2023)
Background: Little is known about the practice of traditional medicinal plants use, especially during pregnancy in Ethiopia. Moreover, there is no previous study conducted on practices and related factors of medicinal plants among pregnant women in Gojjam, northwest Ethiopia. Methods: A multicentered facility-based cross-sectional study was conducted from July 1-30/2021. A total of 423 pregnant mothers on antenatal care were included in this study. To get study participants, multistage sampling techniques were used. Data were collected using a semi-structured interviewer-administered questionnaire. SPSS version 20.0 statistical package was used for statistical analysis. Univariable and multivariable logistic regression analysis was performed to identify factors related to the medicinal plants’ utilization status of pregnant mothers. The study results were presented in both descriptive statistics (percent, table, graph, mean, and dispersion measurements like standard deviation) and inferential statistics (odds ratio). Results: The magnitude of traditional medicinal plants utilization during pregnancy was 47.7% (95%CI: 42.8%-52.8%). Pregnant mothers residing in rural area [Adjusted Odds Ratio (AOR)=3.13; 95% Confidence Interval (CI):1.53, 6.41], being illiterate (AOR=2.99; 95%CI:1.097, 8.17), having illiterate husbands (AOR=3.08; 95%CI:1.29, 7.33), married farmers (AOR=4.92; 95%CI:1.87, 12.94), married merchants (AOR=0.27; 95%CI:0.09, 0.78), having divorced and widowed marital status (AOR=3.93; 95%CI:1.25, 12.395), having low antenatal care visit (AOR=4.76; 95%CI:1.93, 11.74), substance use history (AOR=7.21; 95%CI:3.49, 14.9) and used medicinal plants in previous pregnancy (AOR=4.06; 95%CI:2.03, 8.13) had statistically significant association with medicinal plants use during current pregnancy. Conclusions: The present study revealed that a relatively large number of mothers used medicinal plants of various types during their current pregnancy. Area of residence, maternal educational status, husband’s education level, husband’s occupation status, marital status, number of antenatal care visits, use of medicinal plants in the previous pregnancies and substance use history were among the factors which were significantly associated with the use of traditional medicinal plants during the current pregnancy.